Overexpression of a Banana Aquaporin Gene MaPIP1;1 Enhances Tolerance to Multiple Abiotic Stresses in Transgenic Banana and Analysis of Its Interacting Transcription Factors - Xu, Yi; Liu, Juhua; Jia, Caihong; Hu, Wei; Song, Shun; Xu, Biyu; Jin, Zhiqiang (Frontiers in Plant Science, 2021)
Aquaporins (AQP) can improve the ability of plants to resist abiotic stresses, but the mechanism is still not completely clear. In this research, overexpression of MaPIP1;1 in banana improved tolerance to multiple stresses. The transgenic plants resulted in lower ion leakage (IL) and malondialdehyde (MDA) content, while the proline, chlorophyll, soluble sugar and abscisic acid (ABA) contents were higher. In addition, under high salt and recovery conditions, the content of Na+ and K+ is higher, also under recovery conditions, the ratio of K+/Na+ is higher. Finally, under stress conditions, the expression levels of ABA biosynthesis and response genes in the transgenic lines are higher than those of the wild type. In previous studies, we proved that the MaMADS3 can bind to the promoter region of MaPIP1;1, thereby regulating the expression of MaPIP1;1 and affecting the drought tolerance of banana plants However, the mechanism of MaPIP1;1 gene response to stress under different adversity conditions might be regulated differently. In this study, our study proved that some transcription factor genes, including MaERF14,MaDREB1G, MaMYB1R1, MaERF1/39, MabZIP53 and MaMYB22, showed similar expression patterns with MaPIP1;1 under salt or cold stresses, and their encoded proteins could bind to the the promoter region of MaPIP1;1. Here we proposed a novel MaPIP1;1-mediated mechanism that enhanced salt and cold tolerance in bananas. The results of this study have enriched the stress-resistant regulatory network of aquaporin genes, and are of great significance for the development of molecular breeding strategies for stress-resistant fruit crops.